Cardiac arrhythmias in poorly performing Standardbred and Norwegian–Swedish Coldblooded trotters undergoing high-speed treadmill testing. (January 2021) - Slack, J.; Stefanovski, D.; Madsen, T.F.; Fjordbakk, C.T.; Strand, E.; Fintl, C.
Highlights: The frequency of arrhythmia in any exercise period was high (77–78%) during treadmill testing. Complex ventricular arrhythmias occurred in 15% of horses during the first 2 min of recovery. Maximum heart rate was an excellent predictor of complex ventricular arrhythmias in recovery. Abstract: The significance of cardiac arrhythmias and their possible association with upper airway obstruction are frequently considered in the clinical investigation of poor performance. The specific aims of this retrospective study of a group of poorly performing Standardbred and Norwegian–Swedish Coldblooded trotters were to: (1) describe the overall frequency and frequency distributions of arrhythmias; (2) describe arrhythmia characteristics including percent prematurity, relative recovery cycle lengths and QRS morphology; (3) describe variability of normal RR intervals; and (4) explore possible associations between upper airway abnormalities and arrhythmia categories during peak exercise and recovery. The records of 103 trotters presented to the Norwegian University of Life Sciences for high-speed treadmill testing were reviewed. The occurrence of at least one arrhythmic event was high (77–78%) when considering all exercise periods and 6–10% prematurity criteria. Triplets, salvos, and/or paroxysmal tachyarrhythmias occurred in 8% of horses during peak exercise. Complex ventricular arrhythmias occurred in 15% of horses in the first 2 min of recovery. Evaluation of QRS morphology and return cycle lengths demonstrated areas of overlap in characteristics typically attributed to either supraventricular or ventricular arrhythmias. There was no association between airway diagnosis and arrhythmias during any exercise period. The maximum average HR during peak exercise was an excellent predicter for complex ventricular arrhythmias during recovery. Because perfect categorization of arrhythmias is not possible, future studies should report descriptive arrhythmia information. Prospective studies that evaluate various degrees of upper airway obstruction and the effect on known initiators of arrhythmogenesis are needed.